Oxford international secondary science for grade 6 - Fullick, Ann (Karachi: Oxford University Press., 2024)
Oxford International Secondary Science for Grade 6 is a comprehensive textbook designed to engage students in the exploration of fundamental scientific concepts across various disciplines, including biology, chemistry, and physics. The book emphasizes inquiry-based learning, encouraging students to ask questions, conduct experiments, and analyze results. Each chapter features clear explanations, illustrations, and hands-on activities that promote critical thinking and practical application of scientific principles. With a focus on real-world connections and interdisciplinary approaches, this textbook provides a solid foundation in science, preparing students for further studies in secondary education.